(3QSGdI aj bhGfjf GdefWbs ((3CjhH Hf YKeGf Hf YeQ s)
(3ChdgG (B:s
(3HYO GdHSedI hGdMeO dg CeG HYO agPg QSGdI ai GdefWb CedjJgG dHYV GdGNhGf Ydi SHjd GdGLeGd aUd GddaX GeG OGd HGdeWGHbI s
(3BNQgG (B:s
(3ef BNQ GdehLhO hCeG GdbjGS GdGSJKfGFj aGdHbVjI GdehVhYI dg s
(3Vef eLehY , JQJjHgG (B: 1s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3eJaQbGJs